2015
DOI: 10.1016/j.ejphar.2015.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform changes in membrane receptors in the rat urinary bladder following outlet obstruction

Abstract: The aim of the present study was to investigate the expression and distribution of membrane receptors after bladder outlet obstruction (BOO). Partial bladder outlet obstruction (BOO) was induced in female rats and bladders were harvested after either 10 days or 6 weeks of BOO. The expression of different receptors was surveyed by microarrays and corroborated by immunohistochemistry and western blotting. A microarray experiment identified 10 membrane receptors that were differentially expressed compared to sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…One example is the limited effect of β 3 -adrenoceptor agonists in patients with outlet obstruction [ 44 , 45 ]. Our obstructed rat model has a decreased mRNA level for β 3 -adrenocceptors, and in vitro, the relaxing effect of β 3 -adrenoceptor agonists on pre-contracted rat detrusor strips is almost non-existent [ 46 ]. As the mRNA for β 3 -adrenoceptors is normalized in the de-obstructed bladders, one would expect a more favorable effect on DO by β 3 -adrenoceptor agonists in such bladders.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the limited effect of β 3 -adrenoceptor agonists in patients with outlet obstruction [ 44 , 45 ]. Our obstructed rat model has a decreased mRNA level for β 3 -adrenocceptors, and in vitro, the relaxing effect of β 3 -adrenoceptor agonists on pre-contracted rat detrusor strips is almost non-existent [ 46 ]. As the mRNA for β 3 -adrenoceptors is normalized in the de-obstructed bladders, one would expect a more favorable effect on DO by β 3 -adrenoceptor agonists in such bladders.…”
Section: Discussionmentioning
confidence: 99%
“…Following BOO in rats there are non-uniform changes in bladder membrane receptors (55). Some receptors are upregulated and can be associated with increased agonist responses whereas other can be down-regulated leading to decreased responses.…”
Section: Membrane Receptorsmentioning
confidence: 99%
“…In an additional study, a microarray analysis detected an increase in LGR6 in a rat model of BOO but with no context of possible function. 32 Recently, we expounded on a possible role for Annexin-A1 in treating BOO using a rat model. 33 In those studies, we demonstrated the presence of all six SPM receptors in the rat bladder.…”
Section: Introductionmentioning
confidence: 99%